(untitled) (Tikrit Journal of Veterinary Science, 2025)
This study aimed to investigate the structural development of the brain and cerebellum in local turkeys from hatchling (1 day) to adulthood (2 months, 3-7 months, and adult age). Following euthanasia, the skulls were dissected to extract the cerebellum, which were then rinsed and preserved in 10% neutral buffered formalin for histological analysis. The morphology revealed two cerebellum lobes, Histological examination identified three layers in the cerebellar cortex across all age stages. In the first month, delicate meninges and a few glial cells accompanied small to medium-sized neurons and numerous blood capillaries. As the turkeys aged, there was a notable increase in glial cells and larger, with more developed meninges. Additionally, cavitation’s around neurons and nerve bundles were observed, particularly at one year of age. The cerebellum comprised two layers: an outer cortex with a pial meningeal membrane, consisting of a molecular layer with small nerve cells and glial cells, and a Purkinje layer that increased in size with age. The internal granular layer was broad, filled with small nerve cells and glial cells. Overall, the study concluded that the brain and cerebellum of turkeys exhibit well-developed nerve and glial cell layers, similar to those found in mammals, reflecting significant structural changes as they mature.